2017
DOI: 10.3892/ol.2017.6518
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic effect of arsenic trioxide in lung cancer via inhibition of endothelial cell migration, proliferation and tube formation

Abstract: Abstract. Arsenic trioxide (As 2 O 3 ) exhibits a remarkable effect on leukemia treatment; however, its effect on solid tumors remains poorly explored. The present study demonstrated the inhibitory effect of As 2 O 3 on lung cancer and explored its possible mechanism. It was observed that As 2 O 3 significantly inhibited the growth of lung cancer xenografts and tumor angiogenesis in vivo. The inhibitory effect of As 2 O 3 on cell proliferation in vitro was more remarkable in vascular endothelial cells than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…The effect of W on stem/precursor cell growth does not follow a linear dose-response but rather an inverted U-shaped hormetic model (Calabrese 2004) (Fig. 1), as previously described for other metals such as As, Cd, Cu and Hg (Damelin et al 2000, Hao et al 2009 and specifically reported in embryonic cells of other tissues: human embryo lung fibroblasts for As (Yang et al 2017) and human embryonic kidney 293 cells (HEK 293) for Cd and Hg (Jiang et al 2018). In parallel experiments, we observed that staurosporine-induced apoptosis was more than 30% reduced in thyrospheres exposed to Na 2 WO 4 but again, no effect was observed on mature thyrocyte apoptosis (Fig.…”
Section: :8supporting
confidence: 64%
“…The effect of W on stem/precursor cell growth does not follow a linear dose-response but rather an inverted U-shaped hormetic model (Calabrese 2004) (Fig. 1), as previously described for other metals such as As, Cd, Cu and Hg (Damelin et al 2000, Hao et al 2009 and specifically reported in embryonic cells of other tissues: human embryo lung fibroblasts for As (Yang et al 2017) and human embryonic kidney 293 cells (HEK 293) for Cd and Hg (Jiang et al 2018). In parallel experiments, we observed that staurosporine-induced apoptosis was more than 30% reduced in thyrospheres exposed to Na 2 WO 4 but again, no effect was observed on mature thyrocyte apoptosis (Fig.…”
Section: :8supporting
confidence: 64%
“…We previously reported that As 2 O 3 inhibited the proliferation and colony formation of SCLC cell line [24,25]. Other researchers also reported that As 2 O 3 inhibited the migration and invasion of lung cancer and other solid tumor cells [2628].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, we demonstrated that As 2 O 3 inhibited the growth of lung cancer xenografts, and the inhibitory effect in SCLC was particularly obvious. It was also revealed that As 2 O 3 inhibited angiogenesis in SCLC by downregulating VEGF; As 2 O 3 also influenced the ultrastructure of the endothelial cells and the formation of neovascular lumen by blocking the Dll4-Notch pathway [23,24]. However, whether As 2 O 3 can inhibit the metastasis of SCLC and the possible mechanism involved is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As 2 O 3 not only reduced MVD but also influenced the morphology of blood vessels by inducing the formation of irregular vascular structures with narrow and tortile lumens. Our previous study showed that As 2 O 3 inhibited angiogenesis in lung cancer via the downregulation of VEGF signaling [18, 19] and was accountable for the reduction in microvessels. However, we were unable to explain the change in vessel morphology.…”
Section: Discussionmentioning
confidence: 99%
“…We found that As 2 O 3 significantly reduced microvessel density (MVD) and induced poor development of vascular structures in NCI-H446 cell xenograft models [18]. We also demonstrated that As 2 O 3 restricted the tube formation ability of endothelial cells in vitro [19]. As the effects of As 2 O 3 on angiogenesis regulation were similar to those observed with the blockade of the Notch pathway, we suggest that this pathway may be the antiangiogenic target of As 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%